OPTIMASI JENIS PELARUT DALAM EKSTRAKSI ZAT WARNA ALAM DARI BATANG PISANG KEPOK (Musa paradiasiaca L. cv kepok) DAN BATANG PISANG SUSU (Musa paradiasiaca L. cv susu) - Suarsa, I Wayan; Suarya, Putu; Kurniawati, Ika (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011, 2012)
Research on optimation of the type of solvent in natural dye found in extracs of kepok banana’s stem (Musa paradiasiaca L. cv kepok) and susu banana’s stem (Musa paradiasiaca L. cv susu) has been carried out. The obtained natural dye was determined for its rendement, natural dye groups, and the maximum absorption at 400 – 700 nm. Maseration of 100 g of dry powder of kepok banana and susu banana stems were conducted using four kinds of solvent namely, ethanol, acetone, and n-hexane. From kepok banana’s stem thick extracts 9.21 grams water; 3.19 grams ethanol; 1.23 grams acetone; and 0.21 grams n-hexane were obtained, whereas from susu banana’s stem were 12.13 grams water, 3.31 grams ethanol, 1.42 grams acetone, and 0.17 grams n-hexane thick extracts. Extracts obtained were concentrated, and then the rendements were determined. The redements from the kepok banana’s stem, were : water (36.84%), ethanol (12.67 %), acetone (4.92 %), and n-hexane (0.84%), whereas from susu banana’s stem, were : water (28.52%), ethanol (13.24%), acetone (5.68 %). and n-hexane (0.68%), The result of the fitochemical test showed that the natural dye on kepok and susu banana’s stem using four solvents was flavonoid. whereas tannin on both types of banana’s stem was only found in ethanol, acetone, and n-hexane extracts. Analysis using spectrophotometry UV-vis showed that n-hexane extracts gave the maximum absorption greater than the other solvents. The absorbance of kepok banana’s was 0.992 at 607.0 nm and of susu banana’s was 0.905 at 669.5 nm.
Keywords: banana, maseration, tannin, flavonoid